PENGELOLAAN PEMBELAJARAN PADA SEKOLAH DASAR YANG BERBASIS UASBN (Studi Situs di SD Negeri 01, 03, dan 06 Ungaran) - Dwiharto , Jumani (2011)
The objectives of this research are to describe (1) the characteristic of learning material of Elementary School Based on UASBN in Elementary School State 01, 03, and 06 Ungaran, (2) the characteristic of learning method of Elementary School Based on UASBN in Elementary School State 01, 03, and 06 Ungaran, and (3) the characteristic of evaluation instrument of learning at Elementary School Based on UASBN in Elementary School State 01, 03, and 06 Ungaran. This is qualitative research used ethnography design. This research is conducted in Elementary School State 01, 03, and 06 Ungaran, Semarang. The human resources in this research are principal, teachers and students. The data collecting method used depth interview, observation, and documentation. Analysis of data used arrangement analysis in site for description. Data validity used credibility, transferability, dependability, and conformability. The results of research are (1) the material that is given is condensation material form from fourth grade and in the form of UASBN practices. The practices item is came from school, last year UASBN practices, the exercises from school group, tryout exercises of sub-district and district level. For the material of practices exercise that is given is multiple choices and essay. (2) In learning activity, the method that is used is discourse variation, question and answer, inquiry, and discussion. In learning activity with think pair and share model, 80% of student is actively in discussion with their friend. Interaction among the student is can be seen from the activity of discussion about the exercises item that is discussed and then try to find the answer. In actively, the student is discussed and cooperation in doing exercises item that is given and read the discussion result in front of the class. (3) Learning evaluation is done during in teaching learning activity. Evaluation is given in exercises item form that is come from teacher, last year UASBN exercise evaluation, and tryout. The evaluation form of learning activity is used multiple choices and essay.